[About CEU – Part 10]
The continuation of the series “About CEU” and the third part of the video about the CEU Conference and Residence Center. Contains more images with the Sport Center, specifically the pool. The recording continues with scenes from the party held in the dormitory in one of the major conferences room known as the Budapest Room.